Предмет: Математика, автор: Аноним

найдите значения выражения (2 1/4 - 1 1/4*(2/7+3 1/7*1/3) ) : 0,7=

Ответы

Автор ответа: zhenyaM2002
0
Выражением:
(2  frac{1}{4} - 1 frac{1}{4} * ( frac{2}{7} +3  frac{1}{7} * frac{1}{3} )) :0,7= \  \ 
=  (2frac{1}{4} -  frac{5}{4} *( frac{2*3}{7*3} +  frac{22*1}{7*3} )) :0,7= \  \ 
=( 2 frac{1}{4} - frac{5*28}{4*21} ):0,7= \  \ 
=(  frac{9}{4} - frac{5*1}{1*3} ) :0,7= \  \ 
= frac{9*3- 5*4}{4*3}  : 0,7= \  \ 
= frac{7}{12} * frac{10}{7} = \  \ 
= frac{1*5}{6*1} = frac{5}{6}
По действиям:
(2 frac{1}{4} - 1 frac{1}{4} * ( frac{2}{7} +3 frac{1}{7} * frac{1}{3} )) :0,7=frac{5}{6}\  \ 
1) 3 frac{1}{7} * frac{1}{3}=  frac{22*1}{7*3} = 1frac{1}{21}  \  \ 
2)  frac{2}{7} +1 frac{1}{21} = frac{6+22}{21} = frac{28}{21} = frac{4}{3} =1 frac{1}{3}  \  \ 
3) 1  frac{1}{4} *1 frac{1}{3} = frac{5*4}{4*3} = frac{5}{3} = 1  frac{2}{3}  \  \ 
4) 2  frac{1}{4} - 1  frac{2}{3} = frac{27- 20}{12}= frac{7}{12}  \  \ 
5)  frac{7}{12} : frac{7}{10} = frac{7*10}{12*7} = frac{5}{6}
Похожие вопросы
Предмет: Математика, автор: sofdem95
Предмет: Математика, автор: 0987421